PROPORSI IBU DENGAN PERSEPSI BENAR TENTANG STATUS NUTRISI ANAK - Luh Wayan Puspa Ningsih; Ni Nyoman Metriani Nesa; Nyoman Budi Hartawan (E-Jurnal Medika Udayana, 2020)
Malnutrition is a global problem which contributes to children’s mortality and morbidity. One simple effort to reduce malnutrition is involving mothers to help their children to afford optimal nutritional status. The first step is determining the mother’s perception about their children’s nutritional status. The aim of this study was to determine the correct proportion of mother perception about children’s nutritional status. This was a cross sectional study and conducted on August 2016. Subjects and the respondences were 95 children by ages 4 until 5 years old, from TK Kemala Bhayangkari 04, Gianyar with their mother. Nutritional status components were measured objectively. Meanwhile, the mother’s perceptions were measured by body image sillhouette chart in the questionaire. Feel minus ideal discrepancy (FID) and feel minus actual status inconsistency (FAI) indexes were also measured. The proportion of correct mother’s perception about children nutritional status was 41.10%. Whereas, the highest FID proportion was 50.50% with negative value, which mean the mother wanted their children to be chubbier. The proportion of underestimated perception was 30.50% which mean the mother see their children as thinner than they were. Proportion of correct mothers perception about children nutritional status was still low, mothers wanted their children to be chubbier and consider their children were thinner than they were. Based on the study, the general mother’s perception about children nutritional status should be corrected to prevent malnutrition. Keywords: Nutritional status, mother’s perception, Body image sillhouette chart